Developing a Dual-Method Pedagogical Model for Teaching Islamic Calendar Diversity in Indonesian Schools - Alwy Ahmed Mohamed; Mowafg Masuwd (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to develop a dual-method learning model integrating Hisab and Rukyat to improve students’ understanding, critical thinking, and attitudes toward religious diversity. Theoretical framework: The study is based on constructivist learning theory and Design-Based Research (DBR), emphasizing active learning, comparison, and reflective understanding. Literature review: Previous studies show that separate teaching of Hisab and Rukyat often causes fragmented understanding and confusion among students in Islamic education. Methods: This study uses a qualitative DBR approach through curriculum analysis, teacher interviews, and classroom observations in Muhammadiyah and Nahdlatul Ulama institutions. Results: The findings reveal that segregated teaching of Hisab and Rukyat results in fragmented student comprehension and confusion regarding Islamic calendar determination. In contrast, the implementation of an integrated dual-method pedagogical model enhances students’ conceptual understanding by enabling them to compare and evaluate both approaches simultaneously. The model also promotes critical thinking skills and encourages more inclusive and moderate religious attitudes among students. Implications: The study provides an innovative teaching approach that supports inclusive Islamic education and reduces misunderstandings between different methodologies. Novelty: The novelty of this research is the development of a dual-method pedagogical model that combines Hisab and Rukyat in one integrated classroom learning system.